Hyper nature - Martin, Philippe, 1954-; Firefly Books (Richmond Hill, Ontario : Firefly Books, 2015)
Hyper Nature is a portfolio of Martin's stunning photographs of snails, orchids, dragonflies, snakes, frogs and many other creatures. The hyperrealism and large images bring the viewer into the heart of the scene, face to face with the subject, where he can discover the smallest detail. This is nature photography as never seen before. Martin also explains how he achieves his photographs, increasing readers' appreciation and leaving a legacy for new photographers."--Provided by publisher. The most recent exhibition of Martin's photographs attracted one million visitors to the Luxembourg Gardens in Paris.
Includes index.
Keywords: Martin, Philippe, -- 1954-; Nature photography; Photo-realism.